Peru's economic growth (2006-2010): precarious competitiveness with sustainability risks - Pezo Paredes, Alfredo (2010)
A comparative analysis of the proposals presented by Michael Porter on Peru's economic situation, President Alan García's message to the nation in July 2008, as well as the study presented by CE PAL for the 2009-201 O period, CEPLAN's point of view in its Strategic Plan for National Development, among others, allows us to understand that our growth continues to be based on an export boom that could turn into an “export illusion”, a risk that leads to certain recommendations such as the need to diversify the productive structure, establish clusters and develop aggressive technological innovation processes.